2014
DOI: 10.1002/j.1556-6676.2014.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Identity Development: A Grounded Theory of Transformational Tasks of Counselors

Abstract: The purpose of this qualitative grounded theory study was to investigate practicing counselors' professional identity development at nodal points during their career. Through the use of 6 focus groups of beginning, experienced, and expert counselors, 26 participants shared their experiences, and 6 themes emerged to form a theory of transformational tasks of professional identity development. Through these tasks, counselors encountered issues of idealism toward realism, burnout toward rejuvenation, and compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 28 publications
9
134
0
2
Order By: Relevance
“…Nothing confirms values, beliefs, and identity more consistently than experience. For counselors-in-training and practicing counselors, working with clients confirms the counselor's skills and motivation to work as a counselor (Gibson et al, 2010;Moss et al, 2014). Many times, it prevents burnout and can rejuvenate the counselor by providing direction for professional development.…”
Section: Professional Experiencementioning
confidence: 97%
See 3 more Smart Citations
“…Nothing confirms values, beliefs, and identity more consistently than experience. For counselors-in-training and practicing counselors, working with clients confirms the counselor's skills and motivation to work as a counselor (Gibson et al, 2010;Moss et al, 2014). Many times, it prevents burnout and can rejuvenate the counselor by providing direction for professional development.…”
Section: Professional Experiencementioning
confidence: 97%
“…A second parallel of professional identity and leadership identity development is the reliance on experts, experienced guides, supervisors, teachers, mentors, and/or faculty during specific transitional periods of development (Dollarhide et al, 2013;Gibson, Dollarhide, Leach, & Moss, 2015;Gibson et al, 2010;Moss et al, 2014). In counselor education programs, students rely on faculty and supervisors as they progress from a reliance on expert/book knowledge to counseling clients in practicum and internship.…”
Section: Transitional Guidancementioning
confidence: 98%
See 2 more Smart Citations
“…Emotional wellbeing can directly affect the quality of counselling services (Corey, 2009). Core counselling competencies include how a person relates to him/herself, others and the social environment (Moss et al, 2014). Lambie et al (2010) identified empathy, flexibility, taking alternative perspectives, self-care and emotional wellbeing as key components of effective counselling.…”
Section: Discussionmentioning
confidence: 99%